Mechanical response, twinning, and texture evolution of WE43 magnesium-rare earth alloy as a function of strain rate: Experiments and multi-level crystal plasticity modeling. (September 2019) - Feather, William G.; Ghorbanpour, Saeede; Savage, Daniel J.; Ardeljan, Milan; Jahedi, Mohammad; McWilliams, Brandon A.; Gupta, Nikhil; Xiang, Chongchen; Vogel, Sven C.; Knezevic, Marko
Abstract: This work adapts a recently developed multi-level constitutive model for polycrystalline metals that deform by a combination of elasticity, crystallographic slip, and deformation twinning to interpret the deformation behavior of alloy WE43 as a function of strain rate. The model involves a two-level homogenization scheme. First, to relate the grain level to the level of a polycrystalline aggregate, a Taylor-type model is used. Second, to relate the aggregate level response at each finite element (FE) integration point to the macro-level, an implicit FE approach is employed. The model features a dislocation-based hardening law governing the activation stress at the slip and twin system level, taking into account the effects of temperature and strain rate through thermally-activated recovery, dislocation debris formation, and slip-twin interactions. The twinning model employs a composite grain approach for multiple twin variants and considers double twinning. The alloy is tested in simple compression and tension at a quasi-static deformation rate and in compression under high strain rates at room temperature. Microstructure evolution of the alloy is characterized using electron backscattered diffraction and neutron diffraction. Taking the measured initial texture as inputs, it is shown that the model successfully captures mechanical responses, twinning, and texture evolution using a single set of hardening parameters, which are associated with the thermally activated rate law for dislocation density across strain rates. The model internally adjusts relative amounts of active deformation modes based on evolution of slip and twin resistances during the imposed loadings to predict the deformation characteristics. We observe that WE43 exhibits much higher strain-hardening rates under high strain rate deformation than under quasi-static deformation. The observation is rationalized as primarily originating from the pronounced activation of twins and especially contraction and double twins during high strain rate deformation. These twins are effective in strain hardening of the alloy through the texture and barrier hardening effects. Highlights: A multi-level grain-to-polycrystalline aggregate-to-macro-level model, T-CPFE, is adapted for modeling of WE43. EBSD, neutron diffraction, and mechanical testing data are used to calibrate and validate the model. Anisotropy in mechanical response induced by microstructural evolution is predicted. Role of deformation modes on the mechanical behavior and texture evolution is discussed. Formation of contraction twins is identified to increase the rate of strain hardening under high strain rate deformation.